Comportamiento agronómico de nuevos materiales de maíz (Zea mays l) comparados con testigos comerciales, sembrados durante la época lluviosa del 2014 en Fumisa. - Pérez Pinto, Pedro Wellington (2014)
This research was conducted in Hacienda "Hope" satellite campus located shrimp " La Malanga " Buena Fé Canton , during the winter of 2014 from January to April . Whose length Oeste79 ° 43 ' 09 " South Latitude 01 ° 08' 39.02 " and 120 meters. Treatment were tested as follows : T1 2B688 ; PAC259 T2 ; 2B604 T3 ; DAS3383 T4 ; NB7443 T5 ; NB7253 T6 ; MAXIMUS T7 , T8 DK399 ; PAC105 T9 ; PAC339 T10 ; AVANTA T11 ; T12 DK7088 ; T13 DK1596 ; PAC860 T14 ; T15 Somma ; T16 and T17 PIONEER30K73 MN - 9092. Design " Randomized Complete " ( BBCA ) with 17 treatments, 4 replications was used blocks . Most earliness to flowering was recorded in the commercial control T6 (NB7443) the same that flowered at 47 days. Commercial witnesses who recorded the highest plant height was for the Pac 399.Por DK 259 and elsewhere in inserting ear height the best result was obtained in the new Pac 860 material above the commercial control . Coverage ear and number of ears harvested showed significant statistical differences , being the first variable the new experimental material ; Maximus and commercial control had higher coverage 105 Pac cob ; number of harvested pods was experimental material for the new MN- 9092 , there are few differences with commercial checks evaluated. The length and diameter of the ear ; Commercial witness being present 2B604 the longest and largest diameter which won the 2B688 . In ear uniformity highly significant differences were observed being the new material more uniform Maximus , The highest yield in kg / ha at the AVANTA presented witnesses and commercial relationship 2B688.En Benefit / cost is extracted DK399 and commercial checks with 0.92 NB7443 and 0.86 .